VEGF and Angiopoietins Promote Inflammatory Cell Recruitment and Mature Blood Vessel Formation in Murine Sponge/Matrigel Model. Issue 1 (January 2015) - Sinnathamby, Tharsika; Jin, Tae Yun; Clavet‐Lanthier, Marie‐Élaine; Cheong, Cheolho; Sirois, Martin G.
ABSTRACT A key feature in the induction of pathological angiogenesis is that inflammation precedes and accompanies the formation of neovessels as evidenced by increased vascular permeability and the recruitment of inflammatory cells. Previously, we and other groups have shown that selected growth factors, namely vascular endothelial growth factor (VEGF) and angiopoietins (Ang1 and Ang2) do not only promote angiogenesis, but can also induce inflammatory response. Herein, given a pro‐inflammatory environment, we addressed the individual capacity of VEGF and angiopoietins to promote the formation of mature neovessels and to identify the different types of inflammatory cells accompanying the angiogenic process over time. Sterilized polyvinyl alcohol (PVA) sponges soaked in growth factor‐depleted Matrigel mixed with PBS, VEGF, Ang1, or Ang2 (200 ng/200 µl) were subcutaneously inserted into anesthetized mice. Sponges were removed at day 4, 7, 14, or 21 post‐procedure for histological, immunohistological (IHC), and flow cytometry analyses. As compared to PBS‐treated sponges, the three growth factors promoted the recruitment of inflammatory cells, mainly neutrophils and macrophages, and to a lesser extent, T‐ and B‐cells. In addition, they were more potent and more rapid in the recruitment of endothelial cells (ECs) and in the formation and maturation (ensheating of smooth muscle cells around ECs) of neovessels. Thus, the autocrine/paracrine interaction among the different inflammatory cells in combination with VEGF, Ang1, or Ang2 provides a suitable microenvironment for the formation and maturation of blood vessels. J. Cell. Biochem. 116: 45–57, 2015. © 2014 Wiley Periodicals, Inc.